Effect of optimal shot peening time on fatigue life for aluminum alloy 6061-T651 - Al-Khazraji, Ahmed N. (Al-Khwarizmi Engineering Journal, 2019)
The compressive residual stresses generated by shot peening, is increased in a direct proportional way with shot peening time (SPT). For each metal, there is an optimum shot peening time (O.S.T) which gives the optimum fatigue life. This paper experimentally studied to optimize shot peening time of aluminium alloy 6061-T651 as well as using of and analysis of variance (ANOVA).Two types of fatigue test specimens’ configuration were used, one without notch (smooth) and the other with a notch radius (1,25mm), each type was shot peened at different time. The (O.S.T) was experimentally estimated  to be 8 minutes reaching the surface stresses at maximum peak of -184.94 MPa.A response surface methodology (RSM) is presented to optimize the surface properties of fatigue life due to effect of two parameters (shot peening time and fatigue stresses). A statistical software was used to perform analysis of variance (ANOVA)  to predict the optimum shot peening time. The results were 8.007 minutes without notch and 7.53 minutes with notch. Two 2nd degree polynomials were obtained for the two studied cases with confidence level of 95%. Experimentally26.67% enhancement in fatigue life was obtained, but after using (RSM), the results gave 61% improvement, compared with ref. [2].